Response of Glass Fiber Reinforced Polymer (GFRP)-Steel Hybrid Reinforcing Bar in Uniaxial Tension - Minkwan Ju; Sangyun Lee; Cheolwoo Park (International Journal of Concrete Structures and Materials, 2017)
Abstract This study introduces a glass fiber reinforced polymer (GFRP)-steel hybrid bar with a core of a deformed steel bar (steel core). Six types of the hybrid cross section were considered, and a total of 48 tensile specimens were tested by the uniaxial tensile test to measure the tensile strength and modulus of elasticity of the GFRP hybrid bar. The results of the uniaxial tensile test revealed that the GFRP hybrid bar showed higher modulus of elasticity and lesser ultimate tensile strength than those shown by a normal GFRP bar. The stress–strain relationship showed a bi-linear behavior indicating good ductility against the brittle failure of a normal GFRP bar. Among all the steel core having a diameter of 19.1 mm, the bar with a core diameter of 9.53 mm exhibited the highest tangent modulus of elasticity. A tensile stress–strain model was suggested for the GFRP hybrid bar having an outer diameter of 19.1 mm and a core diameter of 9.53 mm. This was in good agreement with the experimental results. The suggested stress–strain model can be applied for structural design or analysis of concrete structures such as bridge deck slabs.